Constrained Potential: A Characterisation of Mexican Microenterprises - Ana Karen Negrete Garcia (German Institute of Global and Area Studies (GIGA), 2018)
This paper investigates the existence and nature of constraints prevailing among Mexican microenterprises. It provides inter-temporal insights by relying on firm-level data spanning from 1994 to 2012. A performance index is defined based on firm levels of capital stock and monthly profits, and is used to estimate the empirical probability of a business's success. The predicted values are used to classify every microenterprise into one of three categories: upper, middle, or lower segment. Overall, the study provides evidence of constrained productivity and capital misallocation. Specifically, middle-segment firms exhibit entrepreneurial features and their average marginal returns are 15 percent. Because this segment faces mainly external constraints, cost-effective interventions are plausible. Regarding the lower-segment firms, it is estimated that their average monthly marginal returns are 30 per cent, compared to 1 per cent for the upper segment. It is also shown that, over time, the share that middle-segment firms represent relative to all microenterprises increased from 16 to 22 percent. Lastly, the sources of variation in monthly profits among segments are explored using the Oaxaca-Blinder decomposition method.
Keywords: C25; D22; D24; N86; O12; O17; 330; microenterprises; returns to capital; constrained productivity; Mexico; decomposition method; empirical probability